Vietnam, a Hotspot for Chromosomal Diversity and Cryptic Species in Black Flies (Diptera: Simuliidae) - Adler, P.H.; Takaoka, Hiroyuki; Sofian-Azirun, Mohd; Low, Van Lun; Ya'cob, Z.; Chen, Chee Dhang; Lau, K.W.; Pham, X.D. (Public Library of Science, 2016)
The increasing attention on Vietnam as a biodiversity hotspot prompted an investigation of the potential for cryptic diversity in black flies, a group well known elsewhere for its high frequency of isomorphic species. We analyzed the banding structure of the larval polytene chromosomes in the Simulium tuberosum species group to probe for diversity beyond the morphological level. Among 272 larvae, 88 different chromosomal rearrangements, primarily paracentric inversions, were discovered in addition to 25 already known in the basic sequences of the group in Asia. Chromosomal diversity in Vietnam far exceeds that known for the group in Thailand, with only about 5% of the rearrangements shared between the two countries. Fifteen cytoforms and nine morphoforms were revealed among six nominal species in Vietnam. Chromosomal evidence, combined with available molecular and morphological evidence, conservatively suggests that at least five of the cytoforms are valid species, two of which require formal names. The total chromosomal rearrangements and species (15) now known from the group in Vietnam far exceed those of any other area of comparable size in the world, supporting the country’s status as a biodiversity hotspot. Phylogenetic inference based on uniquely shared, derived chromosomal rearrangements supports the clustering of cytoforms into two primary lineages, the Simulium tani complex and the Southeast Asian Simulium tuberosum subgroup. Some of these taxa could be threatened by habitat destruction, given their restricted geographical distributions and the expanding human population of Vietnam.